FLIGHT ACTIVITY OF THE JATAÍ BEE (TETRAGONISCA ANGUSTULA) IN ANÁPOLIS, GOIÁS: PHASE 2 (CIPEEX, 2026)
After completing Phase 1, it was determined that more data was needed to better understand the behavior of the jataí bee in Anápolis. Besides being a stingless species, this insect is essential for ecological balance due to its pollination activity. Therefore, this study provides information on the flight behavior of the jataí bee (Tetragonisca angustula) in Anápolis between May 2024 and September 2025. The study was conducted at UniEvangélica, where a hive from the institution's existing meliponary was selected. Daily, using a Wi-Fi surveillance camera, information on the start and end times and temperatures of these bees' flight activity was recorded. The results demonstrate consistency in flight activity times; however, in atypical cases, such as on days considered cold in the region, the start of bee activity can be delayed by up to four hours.
Keywords: Stingless bee; Climate; Honey; Temperature